Tissue-Specific Induction of Mouse ZIP8 and ZIP14 Divalent Cation/Bicarbonate Symporters by, and Cytokine Response to, Inflammatory Signals. (May 2014) - Gálvez-Peralta, Marina; Wang, Zhifang; Bao, Shengying; Knoell, Daren L.; Nebert, Daniel W.
Mouse Slc39a8 and Slc39a14 genes encode ZIP8 and ZIP14, respectively, which are ubiquitous divalent cation/(HCO3 – )2 symporters responsible for uptake of Zn 2+, Fe 2+, and Mn 2+ into cells. Cd 2+ and other toxic nonessential metals can displace essential cations, thereby entering vertebrate cells. Whereas Slc39a8 encodes a single protein, Slc39a14 has 2 exons 4 which, via alternative splicing, give rise to ZIP14A and ZIP14B; why differences exist in cell type-specific expression of ZIP14A and ZIP14B remains unknown. Inflammatory stimuli have been associated with upregulation of ZIP8 and ZIP14, but a systematic study of many tissues simultaneously in a laboratory animal following inflammatory cytokine exposure has not yet been reported. Herein, we show that C57BL/6J male mice––treated intraperitoneally with lipopolysaccharide or the proinflammatory cytokines tumor necrosis factor (TNF) or interleukin-6 (IL6)––exhibited quantatively very different, highly tissue-specific, and markedly time-dependent up- and downregulation of ZIP8, ZIP14A, and ZIP14B messenger RNA (mRNA) levels in 12 tissues. The magnitude of inflammatory response was confirmed by measuring the proinflammatory cytokine TNF, IL6, and interleukin-1β mRNA levels in the same tissues of these animals. Our data suggest that most if not all tissues use ZIP8, ZIP14A, and/or ZIP14B for Zn 2+ uptake, some tissues under basal conditions and others moreso when inflammatory stressors are present; collectively, this might lead to substantial alterations in plasma Zn 2+ levels due to Zn 2+ redistribution not just in liver but across many vital organs. In the context of cadmium-mediated toxicity, our data suggest that tissues other than liver, kidney, and lung should also be considered.